Type specimens, samples of live individuals and the Galapagos Pink Land Iguana - Donegan, Thomas M. (Zootaxa, 2009)
The nomenclatural implications of Gentile & Snell (2009)'s innovations in the designation of a type specimen - that is sampled and tagged but not killed - are discussed.  The paper also responds to Nemésio (2009)'s criticism of Donegan (2008), where I argued that descriptions based on samples of live individuals are valid.  I also discuss whether recent descriptions of such a nature involve a different degree of scientific rigour to other descriptions.